2018
DOI: 10.1080/13501763.2018.1526204
|View full text |Cite
|
Sign up to set email alerts
|

Neofunctionalism and EU external policy integration: the case of capacity building in support of security and development (CBSD)

Abstract: Under the umbrella of Capacity Building in Support of Security and Development (CBSD), the EU provides equipment and infrastructure to the armed forces of partner countries. The 2017 reform of the Instrument contributing to Stability and Peace (IcSP) to implement CBSD represents a remarkable integrative step at the interface of EU security and development policy. This article explains the IcSP reform through a neofunctionalist lens. It argues that the extension of the Commission's competences in EU security af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
3
11
0
1
Order By: Relevance
“…Kleine, 2014) in the European integration literature. The current study thus confirms the previous empirical observations in such fields, inter alia, as the environment, regional development, research and technological development (Pollack, 1994), critical infrastructure protection (Pursiainen, 2009), energy (Maltby, 2013), civil security (Kirchner et al, 2015), Common Foreign and Security Policy (Bergmann, 2019; Riddervold, 2016; Riddervold & Rosén, 2016), and health policy (Greer & Löblová, 2017).…”
Section: What Explains the Unfinished Europeanization Of Nras?supporting
confidence: 90%
“…Kleine, 2014) in the European integration literature. The current study thus confirms the previous empirical observations in such fields, inter alia, as the environment, regional development, research and technological development (Pollack, 1994), critical infrastructure protection (Pursiainen, 2009), energy (Maltby, 2013), civil security (Kirchner et al, 2015), Common Foreign and Security Policy (Bergmann, 2019; Riddervold, 2016; Riddervold & Rosén, 2016), and health policy (Greer & Löblová, 2017).…”
Section: What Explains the Unfinished Europeanization Of Nras?supporting
confidence: 90%
“…Capacity Building in Support of Security and Development (CBSD), launched in 2017, is another initiative for further integration and coherence in the security and defense area. Through CBSD, the EU aims to fund the equipment and infrastructure of the armed forces of the EU Member States (Bergmann, 2019). As a result of the decision of all EU institutions, the CBSD was put into practice under the Instrument contributing to Stability and Peace (IcSP), which is a financial instrument of the development policy.…”
Section: Moving To Further Integration: Eugs and New Initiativesmentioning
confidence: 99%
“…By doing this, the EU will provide training, equipment, and infrastructure to the armed forces under the decision-making of the European Commission. Therefore, the Commission accessed the supranational power in EU's security affairs and opened a way to use the EU's budget in funding the armed forces (Bergmann, 2019). Same year, the Military Planning and Conduct Capability (MPCC) was also founded.…”
Section: Moving To Further Integration: Eugs and New Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years EU decision‐making processes and the normative underpinnings of EU external relations have been subject to intense debates in the EP, the Council, the media and the streets (Balfour et al, 2016; Thomas, 2017). This has been visible with regard to the EU's stance in the UN Human Rights Council (Klose et al, 2017), sanctions towards Russia (Sjursen and Rosén, 2017), fisheries and trade agreements (De Bièvre et al, 2020; Young, 2016; Zimmermann, 2017), security issues (Bergmann, 2019; Hegemann and Schneckener, 2019; Wagner et al, 2017), trade policy (Gheyle and De Ville, 2017), humanitarian aid (Dany, 2015), and the EU's relations with China (Mohan, 2018). Scholars have suggested that these trends point to the increasing politicization of EU external relations (Costa, 2018; Wagner, 2017).…”
Section: Introductionmentioning
confidence: 99%